LB7. Contract Tracing Investigation Following First Case of Andes Virus in the United States. (26th November 2018) - Kofman, Aaron; Eggers, Paula; Kjemtrup, Anne; Hall, Rebecca; Brown, Shelley; Choi, Mary; Yaglom, Hayley; Duwell, Monique; Knust, Barbara; Klena, John; Alvarado-Ramy, Francisco; Shoemaker, Trevor; et al.
Abstract: Background: In January 2018, a patient admitted to a Delaware hospital tested positive for New World hantavirus by IgM and IgG ELISA. Subsequent testing by CDC's Viral Special Pathogens Branch (VSPB) confirmed Andes virus (ANDV) by reverse transcription polymerase chain reaction (RT-PCR) and sequencing. ANDV is transmitted to humans through contact with long-tailed rice rats endemic to Argentina and Chile. Unlike other hantavirus species, ANDV can be transmitted person to person, but transmission is typically limited to close contacts of ill persons. Because of this risk, a contact tracing investigation was initiated by CDC, state and county health departments. Method: A suspect case was defined as a person with close contact with the traveler who became ill within the maximum incubation period (42 days) following last contact. A high-risk contact was defined as a person with exposure to the traveler's body fluids. A low-risk contact was defined as a person who had provided care or in-flight service to, or was seated near the traveler for at least 1 hour, in the absence of exposure to body fluids. All contacts were advised to self-monitor their temperature daily for 42 days from last contact, and to seek medical care for any of the specified symptoms. Contacts that developed symptoms were tested for ANDV by RT-PCR and serology by VSPB. Result: Fifty-three contacts were identified in six states; 51 were successfully reached. Of these, 28 were healthcare workers, 15 were airline contacts, seven were acquaintances of the traveler, and one was a hospital roommate. Two high-risk contacts were identified, both of whom remained asymptomatic. Six low-risk contacts reported influenza-like illness, diarrhea, or mild rhinitis during the incubation period. All six symptomatic low-risk contacts tested negative for ANDV by PCR, IgM, and IgG. The remaining low-risk contacts remained asymptomatic. Conclusion: Hospitalized patients with ANDV should be managed with standard, contact, and droplet precautions. While the risk of human-to-human transmission is low, contact tracing should be considered to identify potential cases and limit additional exposures. Health providers should consider ANDV in returning travelers with a nonspecific febrile or acute respiratory illness who have traveled to the Andes region of Argentina or Chile in the preceding 6 weeks. Disclosures: All authors: No reported disclosures.